RETRACTED: Toward Sustainable Development: Unleashing the Mechanism Among International Technology Spillover, Institutional Quality, and Green Innovation Capability - Wang, Tao; Ding, Yuan; Gao, Ke; Sun, Ruiqi; Wen, Chen; Yan, Bingzheng (Frontiers in Psychology, 2022)
Under the background of sustainable development, China's economic growth engine turns to innovation-driven, and it is an important way for China to rapidly improve its green innovation capability by opening up to the outside world and utilizing the spillover effect of international technology. In this paper, the system quality evaluation system is reconstructed by the method of fully arranged polygon graphical indicators, and the provincial system quality in China is measured and added into the model as a regulating variable. Dynamic panel method and dynamic threshold panel method are used to test the direct effects of foreign direct investment, foreign direct investment and foreign trade on green innovation capability, the interaction effect of institutional quality and threshold effect. The empirical results show that the three technology spillovers have significantly promoted China's green innovation capability, System quality will affect the determining coefficient of international technology spillovers on China's green innovation capability. The positive promoting effects of foreign direct investment, foreign direct investment and foreign trade on China's green innovation capability all increase with the improvement of China's system quality. Therefore, when utilizing foreign direct investment, foreign direct investment and foreign trade to promote green innovation in each region, each region should consider creating a good institutional environment for the emergence of international technological effects.